Assessment of iodate in food-grade salt based on a smartphone colorimetric platform. - Galiga, Henley F.; Sevilla, Fortunato B. III (2021)
"The regular monitoring of iodized salt available in the household and marketplace is necessary for the effective implementation of the national program of salt iodization to control iodine deficiency and its associated diseases. This study describes a colorimetric measurement of iodate in table salt using a smartphone equipped with application for color analysis and direct readout of iodate levels. The method involved the measurement of the blue component of the colored solution under controlled lighting conditions" - title page.
Includes bibliographical references.
Keywords: Iodates; Iodized salt; Smartphones